Acoustic features of instrumental movie soundtracks elicit distinct and mostly non-overlapping extra-musical meanings in the mind of the listener - Karleigh Groves; Morwaread Mary Farbood; Brandon Carone; Pablo Ripollés; Arianna Zuanazzi (Scientific Reports)
Abstract Music can evoke powerful emotions in listeners. However, the role that instrumental music (music without any vocal part) plays in conveying extra-musical meaning, above and beyond emotions, is still a debated question. We conducted a study wherein participants (N = 121) listened to twenty 15-second-long excerpts of polyphonic instrumental soundtrack music and reported (i) perceived emotions (e.g., happiness, sadness) as well as (ii) movie scene properties imagined during listening (e.g., scene brightness, character role). We systematically investigated how acoustic features of instrumental soundtrack excerpts (e.g., tempo, loudness) contributed to mental imagery of movie scenes. We show distinct and mostly non-overlapping contributions of acoustic features to the imagination of properties of movie scene settings, characters, actions, and objects. Moreover, we find that negatively-valenced emotions fully mediate the relation between a subset of acoustic features and movie scene properties, providing evidence for the importance of emotional valence in evoking mental imagery. The data demonstrate the capacity of music to convey extra-musical semantic information through audition.